(3GdMHS GdEMJjGWj GdJYSaj (B/ s - (3fUQ GdOjf eMehO WGgQ ESeGYjds; (3W`GQb SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhb s ((3fUQ GdOjf eMehO WGgQ ESeGYjd (B: s, 2010)
(3GdMHS GdGMJjGWj GdJYSaj gh GdMHS GdeNGda ddTQhW hGdVeGfGJ GdbGfhfjI (B: (3Ch ZjQ GdVQhQj dSjQ GdJMbjb (B: (3ShGA GfJa`J Yfg g`Pg GdVQhQI GHJOGkA Ce GQJaY`J Yfg HYO Pd`c dJLGhRg GdMO GdeYbhd dUaI GdVQhQI hVeGfGJ GdeMGceI GdYGOdI (B: (3hjKjQ gPG GdELQGA fRGY LOdj Hjf ebJVjGJ GMJQGe GdMQjI GdaQOjI hMb GdOhdI aj GdYbGH hGdeLJeY aj GdCef hGdCeGf (B: (3ceG jKjQ CjVkG JYGQV eY CUd GdHQGAI GdcGef aj cd EfSGf (B: (3hjdMb VQQkG HGdZkG HGdeMHhS GMJjGWjkG JYSajkG ShGA bVj dg HGdHQGAI Ch Ydjg HGdEOGfI (B: (3ceG jUjH BNQjf ZjQg cCaQGO CSQJg (B: (3hgPG GdELQGA GdJYSaj jhLH eSFhdjI GdBeQ Hg HOYhj GdeNGUeI eJj JhGaQJ CMO CSHGHgG (B: (3heSFhdjI GdOhdI HGYJHGQ Cf GdMHS GdGMJjGWj YedkG ef CYeGd GdSdWI GdbVGFjI (B: (3hddeVQhQ ef GdMHS GdGMJjGWj GdJYSaj GdMb aj GdJYhjV GdeGOj hGdCOHj Yf GdCVQGQ GdJj dMbJ Hg LQGA gPG GdMHS GdJYSaj (B: (3hbO cad GdeTQY GdMb aj GdJYhjV hde jfXe MJj GdBf BdjI GdeWGdHI HgPG GdMb hgh eG fgjH Hg Cf jSQY Edjg (B.s
Arbitrary preventive detention is the detention which breaks legal condition and guaranties or unnecessary for the investigations even this necessity was not found from the very beginning or exempted later for exceeding the rational limits for being necessary and for the guaranties of fair judgment.This procedure arises argumental dispute between the respect of the individual freedom and the right of the state to punish and the society to be secure and safe. Also it causes apposition between the origin of being innocent inside every human being and it causes great harm to the detained person even he is sentenced to be guilty or innocent also his family members. This Arbitrary procedure is the responsibility of the person who passed the sentence of the dispute whenever one of its conditions is found, and it is the responsibility of the state. The person who is harmed has the right in both physical and moral compensation. The legislator guarantied this right but he didn't regulate the way to ask for it until now, this is what we ask him to do quickly.
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj (B2010.s
(3HHdjhLQGajG(B: (3UaMGJ (B164-169.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFj GdYGes; (3GdMHSs; (3GdMHS GdEMJjGWj s; (3GdbGfhf GdLfGFj GdeUQjs; (3GdbGfhf GdLfGFjs -- (3aQfSGs; (3GdMHS GGdJYSaj s; (3GdGYJbGd GdJYSajs; (3bGYOI GdNUes; (3GdbHVs; (3GdGYJbGds; (3eHOC GdHQGAI GdCUdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs